Emerging Opportunities for 2D Semiconductor/Ferroelectric Transistor‐Structure Devices. Issue 12 (12th February 2021) - Luo, Zheng‐Dong; Yang, Ming‐Min; Liu, Yang; Alexe, Marin
Abstract: Semiconductor technology, which is rapidly evolving, is poised to enter a new era for which revolutionary innovations are needed to address fundamental limitations on material and working principle level. 2D semiconductors inherently holding novel properties at the atomic limit show great promise to tackle challenges imposed by traditional bulk semiconductor materials. Synergistic combination of 2D semiconductors with functional ferroelectrics further offers new working principles, and is expected to deliver massively enhanced device performance for existing complementary metal–oxide–semiconductor (CMOS) technologies and add unprecedented applications for next‐generation electronics. Herein, recent demonstrations of novel device concepts based on 2D semiconductor/ferroelectric heterostructures are critically reviewed covering their working mechanisms, device construction, applications, and challenges. In particular, emerging opportunities of CMOS‐process‐compatible 2D semiconductor/ferroelectric transistor structure devices for the development of a rich variety of applications are discussed, including beyond‐Boltzmann transistors, nonvolatile memories, neuromorphic devices, and reconfigurable nanodevices such as p–n homojunctions and self‐powered photodetectors. It is concluded that 2D semiconductor/ferroelectric heterostructures, as an emergent heterogeneous platform, could drive many more exciting innovations for modern electronics, beyond the capability of ubiquitous silicon systems. Abstract : The marriage between 2D semiconductors and ferroelectrics results in new functionalities, which could be expected to deliver massively enhanced device performance for existing complementary metal–oxide–semiconductor (CMOS) technologies and add unprecedented applications for next‐generation electronics. Recent progress in using 2D semiconductor/ferroelectric hybrid structures to enable a rich variety of emerging device concepts is critically reviewed.